Blood compatibility evaluation of polydopamine nanoparticles - Li, Sha; Yan, Si-Ming; Zhang, Li-Wei; Yang, Xiao-Yan; Guo, Zhong (Frontiers in Pharmacology, 2025)
IntroductionPolydopamine nanoparticles (PDA NPs) exhibit numerous outstanding characteristics, including simple preparation, broad light absorption, drug binding ability, excellent biocompatibility and adhesive properties, making them suitable for biomedical application. However, the limited information on their hemocompatibility may hinder their progression from laboratory research to clinical application.MethodsIn this study, we investigated comprehensively the hemocompatibility of PDA NPs, assessed the effects of PDA NPs on red blood cells (RBCs) morphology and lysis, fibrinogen structure and conformation, blood coagulation, platelet activation, complement system activation, and organ toxicity.ResultsThe results indicated that PDA NPs can induce morphological changes and hemolysis in RBCs in a concentration-dependent manner. Interactions with fibrinogen suggested a disturbance in the protein’s microenvironment without significantly altering its secondary structure. This study also revealed that PDA NPs have a concentration-dependent effect on blood coagulation, platelet activation, and complement system activation. Additionally, PDA NPs showed no significant acute toxicity after intravenous injection.ConclusionThe findings offer important insights into the hemocompatibility of PDA NPs, which is essential for their safe and effective clinical use. Understanding their interactions with blood components is key to ensuring their compatibility in biomedical applications. These results are vital for guiding the development of PDA NPs for medical use, particularly in blood-contacting applications.